Nilai Perusahaan Sektor Property dan Real Estate: Peran Intellectual Capital, Business Risk, dan Financial Distress - Susi Susilawati; Ariana Sifa Mufliha; Samukri; Maria Suryaningsih (Universitas Muhammadiyah Jakarta, 2026)
Objectives: To analyze the relationship between intellectual capital and business risk on financial distress and its impact on firm value. Design/method/approach: The sample selection method used purposive sampling, selecting 49 property and real estate companies listed on the Indonesia Stock Exchange (IDX). Data analysis used balanced panel data regression, while the indirect effect was tested using the sobel test. Results/findings: The results indicate that intellectual capital does not affect financial distress, whereas business risk has a significant positive impact. Furthermore, intellectual capital and financial distress have a negative effect, while business risk has a significant positive effect on firm value. Financial distress mediates the relationship between intellectual capital and business risk on firm value. Theoretical contribution: This study strengthens the relevance of signaling theory and the risk theoretical framework in explaining how intellectual capital and business risk influence firm value. Practical contribution: Provides implications for management in strengthening intellectual capital, managing business risk, and minimizing financial distress. For investors, these findings help clarify the role of business risk and financial distress in determining a firm's value. Limitations: This study is limited to property and real estate companies. Future research could expand the research object and add other variables to capture financial dynamics more comprehensively